PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA CUCIIN HELMET CARE DI DEPOK - Rafi Fardhasila; Dewi Ningsih (Journal of Research and Publication Innovation, 2025)
This study aims to determine the influence of service quality and price on consumer satisfaction in Cuciin Helmet Care in Depokpopua partially or simultaneously. The research method used is quantitative. The population in this study is 1558. The number of samples used amounted to 94 respondents. The data sources in the study are primary data through surveys, interviews, and questionnaires and secondary data in the form of literature studies and documentation. The data collection method is by way of questionnaire while the data analysis method is by means of multiple linear regression. The results of this study are (1) Partially there is a positive and significant influence between Service Quality on Customer Satisfaction in Cuciin Helmet Care in Depok which can be proven from the simple linear regression equation Y=16.697+0.468X1 (2) Partially there is a positive and significant influence between Price on Consumer Satisfaction in Cuciin Helmet Care in Depok This can be proven from the simple linear regression equation Y=17.728+0.559X2 (3) Simultaneously there is a positive and significant influence between Service Quality and Price on Consumer Satisfaction in Washing Helmet Care In Depok, this can be proven from the multiple linear regression equation Y=17.258+0.097X1+0.453X2.